James Adams papers - Adams, James, 1734-1824.
Commission (1777 January 15) as captain of the 4th company, 5th battalion, Pennsylvania militia in Cumberland County, Pa.; Adam's oath of allegiance (1777 September 16) certified by James Armstrong.; and military pass (1779 June 30) issued to Adams by Frederick Watts.
Revolutionary war army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Armstrong, James, -- active 1777.; Watts, Frederick; Pennsylvania. -- Militia. -- Battalion, 5th.; Pennsylvania -- History -- Revolution, 1775-1783.; Army officers